Explanation of factors affecting the sense of place in religious places of Iran (case examples of historical mosques in Tabriz - Lida Akhlaghi; Asadollah Shafizadeh (اکولوژی انسانی)
The mosque, as a center of worship and society, needs a strong connection with its functional area to continue its dynamic life. This connection with the context is realized through a human, physical and natural connection with the external environment. Religion can play an important role in the sense of place and provide a concept of it. The shape and spatial organization is effective according to the degree of attachment to the building, and any change in the physical and psychological dimensions of the building can be effective on the sense of place.The research is descriptive-analytical and exploratory in nature. which originally used qualitative and quantitativ  methods. The sample size is 20 experts and the sample size is 168 people. To analyze the qualitative data, the foundation data method was used with MXQDA software. To analyze the quantitative data and measure the relationship between the variables, the Pearson correlation method and the simple and multivariate linear regression statistical tests were used to determine the relationship and intensity. It was used for correlation between independent and dependent variables. Path analysis was used to determine the direct and indirect effect of variables on the sense of place. Spss and Amos software were used for these analyses.The results showed that perceptual and physical factors have the greatest effect in inducing a sense of place in the historical mosques of Tabriz, and social and functional factors have less effect. Among the investigated variables, vitality has the highest correlation coefficient and impact on the sense of place. Also, among the investigated mosques, Maqbareh Mosque has the most sense of place according to the visitors. Therefore, all physical, administrative, social and functional factors are effective in creating a sense of place in religious places in Iran, especially Tabriz city.